FREQUENCY OF BELL’S PALSY PATIENTS GETTING STEROIDS AT ONSET OF THEIR SYMPTOMS - Tariq, Muhammad; Aziz, Kamran; Hassan, Faheem Ul (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the frequency of Bell’s palsy patients getting recommended doses of steroids at their first presentation to a general physician within the first 72 hours of onset of their symptoms.Study Design: A descriptive study.Place and Duration of Study: Combined Military Hospital (CMH) Lahore, form Nov 2014 to Feb 2015 over a period of four months.Material and Methods: Patients suffering from Bell’s palsy, reporting to a general physician within the first 72 hours of onset of their symptoms and then later visiting CMH Lahore for a second opinion of neurologist. Information about their initial treatment was obtained from the first prescription of their first general physician.Results: Thirty two patients fulfilled the inclusion criteria of our study, 11 (34%) patients received recommended doses of steroids, 14 (44%) received suboptimal doses and 7 (22%) did not receive steroids.Conclusion: Majority of the patients suffering from Bell’s palsy did not received their optimal doses of steroids when they first reported to a general physician after onset of their symptoms.